COLLABORATION OF SCHOOLS AND ESTABLISHMENTS OF HIGHER PEDAGOGICAL EDUCATION: PROBLEMS AND PROSPECTS - Tetіana Potapchuk (Vasyl Stefanyk Precarpathian National University, 2018)
In the article, generalizing the main theoretical foundations of competent professional education, its structural organization, system-based parameters of quality, the general prospects of optimization of the system of professional development of the teacher focused on self-development are determined: a) overcoming the priority of the information-reproductive system of postgraduate education, methods and technologies of its realization, orientation on averaged, typical level of professional activity of a teacher; b) provision of a teacher's subject position in the process of professional development and self-development, programming of methods for increasing professional competence; c) promoting the transition from external management to the self-management process, activating the processes of self-diagnosis, self-analysis, and programming itself; d) Overcoming formalism in the process of professional self-development, in particular targeting external subjects of control and assessment of the level of professional competence of the teacher; e) strengthening of the practical orientation of the professional self-development of the teacher. Key words: institutions of higher pedagogical education, educational space, integrated space, educational cluster, competency education.